2022
DOI: 10.3837/tiis.2022.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Drug distribution management system based on IoT

Abstract: In hospitals and pharmacies, the distribution of medicines is an important part. Any mistakes, misses, fake medicines and expired medicines can cause medical accidents. With the widespread application of the Internet of Things technology (IoT), traditional drug distribution methods need to be upgraded. This article proposes a drug distribution management scheme based on the Internet of Things technology. In the production of drugs, a flexible RFID tag was printed on the packaging box, which stored a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The third novelty of this proposal regarding the state of the art is the comparative study of the different solutions for labelling and reading data on drug packages (IoT, RFID UHF, RFID NFC and barcodes/QR), considering economic as well as operational and environmental aspects. The results improve the state of the art since existing studies do not compare the four possibilities together ( Liu et al, 2022 ; Ruan et al, 2018 ; Camacho-Cogollo, Bone & Iadanza, 2020 ; Lee et al, 2019 ; Haddara & Staaby, 2018 ; Ebrahimzadeh et al, 2021 ; Vagaš et al, 2019 ; Ko & Woo, 2018 ; Zhang, Fu & Li, 2019 ; Buthelez et al, 2022 ; Cocian, Morales & Schneider, 2023 ; Petro et al, 2009 ; Iadanza, 2012 ; Wu, Kuo & Liu, 2005 ; Bevilacqua et al, 2013 ). In contrast, this study has analysed the four technologies and has shown the advantages and disadvantages of Barcode/QR, RFID and IoT for drug management in hospitals.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The third novelty of this proposal regarding the state of the art is the comparative study of the different solutions for labelling and reading data on drug packages (IoT, RFID UHF, RFID NFC and barcodes/QR), considering economic as well as operational and environmental aspects. The results improve the state of the art since existing studies do not compare the four possibilities together ( Liu et al, 2022 ; Ruan et al, 2018 ; Camacho-Cogollo, Bone & Iadanza, 2020 ; Lee et al, 2019 ; Haddara & Staaby, 2018 ; Ebrahimzadeh et al, 2021 ; Vagaš et al, 2019 ; Ko & Woo, 2018 ; Zhang, Fu & Li, 2019 ; Buthelez et al, 2022 ; Cocian, Morales & Schneider, 2023 ; Petro et al, 2009 ; Iadanza, 2012 ; Wu, Kuo & Liu, 2005 ; Bevilacqua et al, 2013 ). In contrast, this study has analysed the four technologies and has shown the advantages and disadvantages of Barcode/QR, RFID and IoT for drug management in hospitals.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, individual reading is common. Finally, neither barcodes nor QR is capable of carrying out tracing and real-time tracking of the source of products ( Liu et al, 2022 ).…”
Section: Disruptive Information Technologies For Drug Management: Rel...mentioning
confidence: 99%
See 3 more Smart Citations